"A Lady of Many Firsts": Press Coverage of the Political Career of Mississippi's Evelyn Gandy, 1948-83. Issue 4 (2nd October 2017) - Smith, Pete
Abstract : For three decades, Mississippi politician Evelyn Gandy was perhaps the most recognized figure in the state. Beginning in 1948, she served in various elected positions, including state assistant attorney general, state treasurer, and commissioner of public welfare. She was elected lieutenant governor in 1976, the first woman to hold the office, before making two unsuccessful gubernatorial bids. Three press frames emerge from the news coverage of Gandy's career: a "first" frame, which presents women's political contributions as an anomaly; frames emphasizing stereotypical gender roles; and an "iron magnolia" frame, an attempt by the news media to acknowledge her growing political assertiveness while overemphasizing stereotypical feminine characteristics. These three frames are problematic, given the news media's power to reinforce gender roles in narrow and limiting ways.